Biological and clinical correlates of the patient health questionnaire-9: exploratory cross-sectional analyses of the baseline health study. Issue 1 (4th January 2022) - Califf, Robert M; Wong, Celeste; Doraiswamy, P Murali; Hong, David S; Miller, David P; Mega, Jessica L
Abstract : Objectives: We assessed the relationship between the Patient Health Questionnaire-9 (PHQ-9) at intake and other measurements intended to assess biological factors, markers of disease and health status. Design, setting and participants: We performed a cross-sectional analysis of 2365 participants from the Baseline Health Study, a prospective cohort of adults selected to represent major demographic groups in the USA. Participants underwent deep phenotyping on demographic, clinical, laboratory, functional and imaging findings. Importance: Despite extensive research on the clinical implications of the PHQ-9, data are limited on the relationship between PHQ-9 scores and other measures of health and disease; we sought to better understand this relationship. Interventions: None. Main outcomes and measures: Cross-sectional measures of medical illnesses, gait, balance strength, activities of daily living, imaging and laboratory tests. Results: Compared with lower PHQ-9 scores, higher scores were associated with female sex (46.9%–66.7%), younger participants (53.6–42.4 years) and compromised physical status (higher resting heart rates (65 vs 75 bpm), larger body mass index (26.5–30 kg/m 2 ), greater waist circumference (91–96.5 cm)) and chronic conditions, including gastro-oesophageal reflux disease (13.2%–24.7%) and asthma (9.5%–20.4%) (p<0.0001). Increasing PHQ-9 score was associated with a higher frequency of comorbidities (migraines (6%–20.4%)) and active symptoms (leg cramps (6.4%–24.7%), mood change (1.2%–47.3%), lack of energy (1.2%–57%)) (p<0.0001). After adjustment for relevant demographic, socioeconomic, behavioural and medical characteristics, we found that memory change, tension, shortness of breath and indicators of musculoskeletal symptoms (backache and neck pain) are related to higher PHQ-9 scores (p<0.0001). Conclusions: Our study highlights how: (1) even subthreshold depressive symptoms (measured by PHQ-9) may be indicative of several individual- and population-level concerns that demand more attention; and (2) depression should be considered a comorbidity in common disease. Trial registration number: NCT03154346 .